2019
DOI: 10.1177/2474126419857207
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation of a Scleral-Fixated, Hydrophobic, Single-Piece Acrylic Intraocular Lens Secondary to Eyelet Fracture From Gore-Tex Suture

Abstract: Purpose: This article reports a case of the dislocation of a scleral-fixated enVista MX60 (Bausch + Lomb) intraocular lens (IOL) secondary to eyelet fracture at the point of contact with a Gore-Tex (W.L. Gore & Associates) suture. Methods: A case report is discussed. Results: An 81-year-old woman presented with decreased vision secondary to a dislocated Gore-Tex scleral-sutured enVista MX60 IOL in the left eye 14 months after surgery. The patient returned to the operating room for IOL exchange, and intraop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…13 Lens fracture at the haptic arm has been reported after fixation by the tying suture around the haptic itself, and there is a recent report of a lens dislocation because of EnVista eyelet fracture. 10,11 We report our own experience with three fractures that occurred using the SOH method with Gore-Tex suture fixation to the sclera. One of the dislocations occurred intraoperatively inside the eye from overtightening the suture with an MX60E lens, which has demonstrated lower tensile strength than the MX60 lens in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Lens fracture at the haptic arm has been reported after fixation by the tying suture around the haptic itself, and there is a recent report of a lens dislocation because of EnVista eyelet fracture. 10,11 We report our own experience with three fractures that occurred using the SOH method with Gore-Tex suture fixation to the sclera. One of the dislocations occurred intraoperatively inside the eye from overtightening the suture with an MX60E lens, which has demonstrated lower tensile strength than the MX60 lens in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 The Gore-Tex suture has been used off-label to fixate this lens to the sclera, usually 2–3 mm from the limbus. 11…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous reports of eyelet breakage from MX60 occurring after Gore-Tex scleral fixation. 13,14 One tension study showed that the MX60E is particularly susceptible to eyelet breakage. 15 In comparison, the CZ70BD is a rigid IOL that must utilized a 7 mm scleral tunnel incision for insertion.…”
Section: Iol Choicementioning
confidence: 99%
“…A foldable one-piece hydrophobic acrylic lens with an eyelet at each optic haptic junction (enVista MX60, Bausch and Lomb, Bridgewater, NJ) has been used for this purpose [47]. However, this lens has thick square haptics, not suitable for sulcus placement, and there is a recent report of eyelet fracture leading to lens dislocation following Gore-Tex fixation of enVista lens [51].…”
Section: Choice Of Iolmentioning
confidence: 99%